Palembang City High School Mover’s Use of School Digitalization to Enhance Learning Quality - Khairani, Neneng; Wardiah, Dessy; Fahmi, Muhammad (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This research aims to explore and analyze the impact of implementing school digitalization to improve the quality of learning in Palembang City High School mover. The study uses a qualitative approach with a descriptive method and was conducted at SMA Negeri Sumatera Selatan, SMA LTI IGM Palembang, and SMA Negeri 18 Palembang. Data collection techniques included interviews, field observations, and documentation studies. The results show that the implementation of digitalization has contributed to enhancing the quality of learning. School digitalization provides opportunities for teachers and students to experience a more flexible and effective learning process tailored to individual needs. It has been integrated into various aspects, such as the learning system, diverse learning media, school administration, student activities, and teacher development. This study is useful for providing additional information about school digitalization and its benefits in relation to the quality of education currently being implemented in Indonesia.